(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
The theoretical and practical situation of the content of problems in teaching the method of using decorative painting elements in "Fine Art" classes in secondary schools was studied and analyzed.